Knowledge and Attitude Among the Saudi Dentists Towards Coronectomy of Impacted Mandibular Third Molars - Raqe Alqhtani N; Mohammed AlThobaiti S; Khalid AlOwais H; Abdulrhman Alabdulkarim M; Abdullah Aldossary R; Tabassum N; AlOtaibi M; Almeslet A (Dove Medical Press, 2022)
Nasser Raqe Alqhtani,1 Sarah Mohammed AlThobaiti,2 Hayat Khalid AlOwais,2 Muneera Abdulrhman Alabdulkarim,2 Reef Abdullah Aldossary,2 Nafeesa Tabassum,3 Mohammed AlOtaibi,4 Asma Almeslet5 1Department of Oral and Maxillofacial Surgery and Diagnostic Science, College of Dentistry, Prince Sattam Bin Abdulaziz University, Al-Kharj, Saudi Arabia; 2College of Dentistry, Riyadh Elm University, Riyadh, Saudi Arabia; 3Department of Diagnostic Sciences, College of Dentistry, Dar Al Uloom University, Riyadh, Saudi Arabia; 4Department of Oral and Maxillofacial Surgery, Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 5Department of Oral Maxillofacial Surgery and Diagnostic Sciences, Riyadh Elm University, Riyadh, Saudi ArabiaCorrespondence: Nasser Raqe Alqhtani, Department of Oral and Maxillofacial Surgery and Diagnostic Science, College of Dentistry, Prince Sattam Bin Abdulaziz University, Al-Kharj, Saudi Arabia, Email dr.nasser@live.co.uk Nafeesa Tabassum, Department of Diagnostic Sciences, College of Dentistry, Dar Al Uloom University, Riyadh, Saudi Arabia, Tel +966577462974, Email nafeesatabassum8@gmail.comPurpose: Compared to the complete extraction of impacted third molars that are in close proximity to the mandibular canal, the coronectomy procedure is used as an alternative, owing to its minimal risk of damaging the Inferior alveolar nerve. Despite clear coronectomy concepts mentioned in the literature, the procedure is debatable. This study aimed to assess the knowledge and attitude towards the coronectomy procedure among dentists in Saudi Arabia.Patients and Methods: The 16 close-ended questionnaire was distributed electronically to 377 dentists over the country. It included the demographic data and the options given to their patients with complicated impacted third molars, and the number of coronectomy they have performed. The retrieved data were exported and transferred to the SPSS software program for analysis. The Chi-squared and Fisher's exact tests were used as appropriate for comparisons. A P-value < 0.05 was considered significant.Results: Only 54 (15%) participants performed coronectomy procedure, and only 28.3% of the participants advised their patients to do coronectomy. Nearly two-thirds of the participants (71.9%) were aware of coronectomy procedures, with no significant differences (P> 0.05) between the groups. About 68.9% of the participants agreed that coronectomy aims to protect inferior alveolar nerve damage. More than 60% of participants believed that coronectomy is a reliable technique, while 40.6% of participants claimed that they were capable of deciding whether to do coronectomy or extraction. No significant differences were found between the groups concerning most of the study variables (P> 0.05).Conclusion: Knowledge of Saudi dentists towards coronectomy is good, while their attitude is still low. More learning strategies about coronectomy should be implemented.Keywords: coronectomy, impacted teeth, knowledge, attitude, inferior alveolar nerve damage, complicated exodontia, third molars